Second-Hand Car Price Estimation Using Machine Learning - Kütükde, Şule (MEF Üniversitesi, Fen Bilimleri Enstitüsü, 2018)
The ones who think to sell their cars always think about their cars’ second-hand market worth, at first. Both for the sellers and the buyers, it is crucially important to estimate the car’s realistic worth, in order not to suffer a loss of money or time. In this research, arabam.com’s advertisement data is obtained with the help of web scraping technique, and later machine learning algorithms like Linear Regression, Decision Tree, Random Forest and Gradient Boosting are applied for collected advertisement data in order to estimate cars’ prices. In addition, some hyperparameter tuning is applied for robust estimation. The models’ performances are discussed, and some remarks offered for further researches.

Arabasını satmak isteyen herkes, ilk olarak arabasının ikinci el araba pazarındaki değerinin ne olduğunu merak eder. Hem alıcılar hem de satıcılar için arabanın değerini gerçekçi olarak tahmin etmek, para yada zaman kaybına uğramamak için son derece önemlidir. Bu çalışmada arabam.com’un ilan verileri web veri çekimi tekniği ile edinildi. Ardından, Lineer Regresyon, Karar Ağacı, Rastgele Orman ve Gradyan Artırma gibi makine öğrenmesi algoritmaları kullanılarak arabaların fiyatları tahmin edilmiştir. Ek olarak, daha güçlü bir tahmin için algoritmaların üst değişkenleri ayarlanmıştır. Modellerin performansı tartışılmış ve gelecek çalışmalar için bazı açıklamalar yapılmıştır.
Makine öğrenmesi kullanarak ikinci el araba fiyatlarının tahmin edilmesi
Keywords: Second-Hand Car; Price Estimation; Machine Learning; Web Scraping; Linear Regression; Decision Tree; Random Forest; Gradient Boosting; Hyperparameter Tuning; İkinci El Araba; Fiyat Tahmini; Makine Öğrenmesi; Web Veri Çekimi; Lineer Regresyon; Karar Ağacı; Rastgele Orman; Gradyan Artırma; Üst Değişken Ayarlama